2020
DOI: 10.1038/s41598-020-60305-x
|View full text |Cite|
|
Sign up to set email alerts
|

A predominant involvement of the triple seropositive patients and others with rheumatoid factor in the association of smoking with rheumatoid arthritis

Abstract: the major environmental risk factor for rheumatoid arthritis (RA) is smoking, which according to a widely accepted model induces protein citrullination in the lungs, triggering the production of anticitrullinated protein antibodies (ACPA) and RA development. Nevertheless, some research findings do not fit this model. Therefore, we obtained six independent cohorts with 2253 RA patients for a detailed analysis of the association between smoking and RA autoantibodies. our results showed a predominant association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
(94 reference statements)
1
15
1
Order By: Relevance
“…Another aspect that could affect the reproducibility of the findings pertains to differences in the patient populations. In this respect, the frequency of smokers was lower in our patients than in some other European EA cohorts [37][38][39] . However, we did not find that smoking alters the association of antibody concordance with the RA classification.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Another aspect that could affect the reproducibility of the findings pertains to differences in the patient populations. In this respect, the frequency of smokers was lower in our patients than in some other European EA cohorts [37][38][39] . However, we did not find that smoking alters the association of antibody concordance with the RA classification.…”
Section: Discussioncontrasting
confidence: 69%
“…The same report showed that the distinction in RF levels added little to classification. This could be explained by the correlation between high RF levels and anti-CCP presence observed in our patients ( Supplementary Table S6) and in other sets of RA patients [38][39][40] . Therefore, the lack of reliance on the RF and anti-CCP levels will permit increasing reproducibility of the RA classification based on anti-AcOrn concordance without losing accuracy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Studies have shown that carbamylation plays a role that is like citrullination in RA [ 249 , 254 , 255 ]. Similar to RF and ACPAs, anti-CarP antibodies show an association with risk when combined with smoking [ 256 ]. The presence of RF is associated with positivity for both ACPAs and anti-CarP antibodies [ 257 ].…”
Section: Carbamylation In Ramentioning
confidence: 99%
“…Exposition to free crystalline silica represents another air pollutant risk-factor retrieved to be associated with RA development (OR = 1.94; CI95: 1.46–2.58), and such association is additive among tobacco smokers seropositive for ACPA and/or RF in men (OR = 3.30; CI95: 2.40–4.54) [ 15 , 64 ]. The underlying pathways leading to the development of RA within individuals exposed to tobacco smoking and air pollutants is still unclear and several models have been proposed: (i) an impaired innate immune system that relies on the positive association between smoking and P. gingivalis [ 65 ]; (ii) an affected adaptive immune response explaining that never smoker RA patients possess elevated protective anti- P. gingivalis and anti-PPAD antibody titers [ 66 ]; (iii) a deregulated PAD4 expression in the lung based on the observation that RA patients with ILD have increase PAD4 expression at transcriptional and protein level in bronchoalveolar granulocytes and monocytes among smokers [ 67 ]; (iv) a higher systemic inflammation as retrieved in the elevated tobacco consumption subgroup [ 17 ]; and (v) an association with RF-positivity (OR = 2.35; IC95: 1.64–3.35) independent from ACPA/CarpA status [ 15 , 68 ]. Although all these explanations are plausible, more studies are warranted to elucidate the mechanisms and their interplay.…”
Section: Factors Associated With a Mucosal Originmentioning
confidence: 99%